2020
DOI: 10.1103/physrevb.102.245203
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Fe 3d impurity band state as the origin of high Curie temperature in the p -type ferromagnetic semiconductor (Ga,Fe)Sb

Abstract: Fex)Sb is one of the promising ferromagnetic semiconductors for spintronic device applications because its Curie temperature (TC) is above 300 K when the Fe concentration x is equal to or higher than ~0.20. However, the origin of the high TC in (Ga,Fe)Sb remains to be elucidated. To address this issue, we use resonant photoemission spectroscopy (RPES) and first-principles calculations to investigate the x dependence of the Fe 3d states in (Ga1-x,Fex)Sb (x = 0.05, 0.15, and 0.25) thin films. The observed Fe 2p-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…In the field of spintronics, dilute magnetic semiconductors (DMSs) that simultaneously provide intrinsic ferromagnetism and semiconducting properties can be achieved by substituting cations in conventional semiconductors with transition metals (TMs) or rare-earth elements, which have attracted much attention in recent decades. [1][2][3][4][5] Among these semiconductors, the III-V GaSb-based DMSs have attracted a large amount of research interest because of their possible high T C values and intrinsic ferromagnetism, [6][7][8][9][10][11][12][13][14][15] which are critical in applications. Sato et al theoretically predicted that the T C of Mn-doped GaSb would be proportional to the Mn concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of spintronics, dilute magnetic semiconductors (DMSs) that simultaneously provide intrinsic ferromagnetism and semiconducting properties can be achieved by substituting cations in conventional semiconductors with transition metals (TMs) or rare-earth elements, which have attracted much attention in recent decades. [1][2][3][4][5] Among these semiconductors, the III-V GaSb-based DMSs have attracted a large amount of research interest because of their possible high T C values and intrinsic ferromagnetism, [6][7][8][9][10][11][12][13][14][15] which are critical in applications. Sato et al theoretically predicted that the T C of Mn-doped GaSb would be proportional to the Mn concentration.…”
Section: Introductionmentioning
confidence: 99%
“…As a key material in the spintronics field, FM semiconductors combined with FM and semiconductors' properties can be prepared by substituting transition metal (TM) or rare-earth elements for cations in traditional semiconductors, 1,2) and have become one of the hotspots in the past decades. Among numerous semiconductors, GaSb has attracted much attention because of its excellent qualities, such as extremely high electron mobility, [3][4][5][6][7][8][9][10][11][12] good lattice matching with other III-V compounds and so on. However, the origin of ferromagnetism remains to be discordant.…”
Section: Introductionmentioning
confidence: 99%
“…However, the origin of ferromagnetism remains to be discordant. You et al suggested high (low) Curie temperature (T C ) mainly comes from high (low) impurity concentrations, and the origin of high T C in (Ga, Fe)Sb is not due to the carrier mechanism, 3) Takeda et al indicated that the enhancement of the double-exchange interaction between minority-spin e electrons with increasing Fe concentration is the origin of the high T C in (Ga, Fe)Sb, 5) while Tu et al reported that the T C of (Ga 1−x Fe x )Sb depends on x and hole concentration, as in the case of hole-induced ferromagnetism. 6) Wang et al predicted FM half-metallic properties and high T C in GaSb:Mn by the first-principles study, 9) while Yin et al attributed the observed ferromagnetism to MnSb second phase.…”
Section: Introductionmentioning
confidence: 99%